UPAYA MENGOPTIMALKAN EDUKASI SWAMEDIKASI DIARE PADA ANAK DI DESA RIMO MUNGKUR KECAMATAN NAMORAMBE KABUPATEN DELI SERDANG PROVINSI SUMATERA UTARA - Sembiring, Pintata (Jurnal Pengabdian Masyarakat Putri Hijau, 2024)
Background: Self-medication is the selective use of modern and traditional medicine by individuals to treat disease. The pharmacist's role in this case is very important to ensure that patients receive appropriate, effective and safe medication and treatment in accordance with therapeutic goals. Aim: This service is to change people's mindset and perspective so that patients can better respond to information about children's diarrhea which can be done by themselves using the Cross-diarrhea Treatment Guidelines. Method: This service takes the form of Health Education in the pharmaceutical sector using a cross-sectional design method that explores risk factors and effects through an observational approach or collecting data at the same time. Results: This study shows that post-service patient knowledge about treating diarrhea in children and self-medication for diarrhea in children is superior in terms of correct use of medication, and in terms of correct and correct use of medication in daily life the patient has carried it out correctly. . Conclusion: The role of pharmacists regarding the suitability of self-medication for diarrhea using the Cross Diarrhea Guidelines is positive in providing knowledge and lessons for posyandu mothers in Rimo Mungkur Village, Namorambe District